The Hippo Pathway and Viral Infections - Wang, Zhilong; Lu, Wanhang; Zhang, Yiling; Zou, Feng; Jin, Zhigang; Zhao, Tiejun (Frontiers in Microbiology, 2020)
The Hippo signaling pathway is a novel tumor suppressor pathway, initially found in Drosophila. Recent studies discover that the Hippo signaling pathway plays a critical role in a wide range of biological processes, including organ size control, cell proliferation, cancer development, and virus-induced diseases. In this review, we summarize the current understanding of the biological feature and pathological role of the Hippo pathway, especially focusing on current findings in the function of the Hippo pathway in virus infection and pathogenesis.